A novel evaluation model for improving trust level of infrastructure as a service - Alabool, H.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
This study intends to propose an effective evaluation model for Infrastructure as a Service (IaaS) in cloud environment. The main goal of this evaluation model is to help IaaS cloud providers to identify the gaps that have not improved according to particular trust evaluation criteria. To achieve that, an integrated model is proposed combining fuzzy set theory and Important Performance Analysis (IPA) technique for evaluating IaaS cloud based trust. The results show that evaluation model can provide some guidelines and suggestions to IaaS cloud service providers on how to improve overall IaaS trust so that they can guarantee business continuity for minimizing service damage. Â© 2015 IEEE.